(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Umbilical cord cross sectional area is an easily obtained sonographic measurement with highly reliable intra and inter observer reproducibility. This study showed a significant correlation between Umbilical cord cross sectional area and birth weight. There is significant association between lean cord and low APGAR score and meconium stained liquor. Umbilical cord cross sectional area can be combined with other fetal biometric parameters to improve the accuracy of identifying the fetus at risk allowing us to manage effectively and thus improves the perinatal outcome.